An atypical spontaneous song by Abbott's Babbler Trichastoma abbotti - Nash, Stephen V; Nash, Anne D (KUKILA, 1987)
The jungle babblers Timaliidae as a whole are renowned vocalists, more easily identified by their collectively varied songs than by their muted plumages. Surprisingly, the ornithological literature is incomplete concerning the repertoires of individual babbler species, as well as for noting regional (or racial) differences. The song of the Abbott's Babbler Trichastoma abbotti in south-eastern Sumatra has recently been the subject of a note in Kukila (Nash & Hash 1985), describing the full adult song of the male bird, and the duelling call notes of the female. Further studies of this species by the authors have revealed an unusual additional song by the male, a ten-note spontaneous 'foraging' song. This song was recorded in the Padang-Sugihan Wildlife Reserve, South Sumatra province, at approximately 0745 hrs. on 12 September 1985, in riverine swamp forest. The recorded song was examined on a Unigon 4500 Uniscan Spectrum Analyzer, and the sonogram was made on a Kay Digital Sono-Graph 7800 set to a wide (300 Khz) band range.